Peroxisomal ATP Uptake Is Provided by Two Adenine Nucleotide Transporters and the ABCD Transporters - van Roermund, Carlo W. T.; IJlst, Lodewijk; Linka, Nicole; Wanders, Ronald J. A.; Waterham, Hans R. (Frontiers in Cell and Developmental Biology, 2022)
Peroxisomes are essential organelles involved in various metabolic processes, including fatty acid -oxidation. Their metabolic functions require a controlled exchange of metabolites and co-factors, including ATP, across the peroxisomal membrane. We investigated which proteins are involved in the peroxisomal uptake of ATP in the yeast Saccharomyces cerevisiae. Using wild-type and targeted deletion strains, we measured ATP-dependent peroxisomal octanoate -oxidation, intra-peroxisomal ATP levels employing peroxisome-targeted ATP-sensing reporter proteins, and ATP uptake in proteoliposomes prepared from purified peroxisomes. We show that intra-peroxisomal ATP levels are maintained by different peroxisomal membrane proteins each with different modes of action: (1) the previously reported Ant1p protein, which catalyzes the exchange of ATP for AMP or ADP, (2) the ABC transporter protein complex Pxa1p/Pxa2p, which mediates both uni-directional acyl-CoA and ATP uptake, and (3) the mitochondrial Aac2p protein, which catalyzes ATP/ADP exchange and has a dual localization in both mitochondria and peroxisomes. Our results provide compelling evidence for a complementary system for the uptake of ATP in peroxisomes.